Comparative analysis of digital services and their impact on the trade segment development - Pirogova Oksana; Zasenko Vilena (E3S Web of Conferences, 2023)
Modern technologies have penetrated into all spheres of human life. At the same time, digital technologies continue to develop at a rapid pace, some areas of activity have achieved high rates in the introduction and application of modern technologies. Digital platforms can be used by all participants in the real estate market. Services are actively used and developed that simplify the interaction between the developer, the buyer and banks, constructors to strengthen developers’ websites, technologies for construction and real estate management, services for appraising an apartment, obtaining a mortgage, legal support, checking debts, encumbrances and history of an apartment, tools for remote demonstration of objects. The ability to use, compare, choose the most appropriate service for a specific request is relevant in modern conditions. The aim of the work is to compare digital services in the field of real estate and make a forecast for the development of the retail segment. The work used the method of comparing the characteristics of the objects of study, correlation and regression analysis. As a result of the study, a sales price forecast for the retail segment was determined and the most informative digital platform in the real estate industry was identified.